Becoming teacher, becoming researcher: reconsidering data analysis in post-qualitative practitioner research. Issue 2 (3rd April 2019) - Lambert, Louise
ABSTRACT: This paper draws on my own research attempts to reconsider the complexities of teacher becomings using creative methodologies. It explores the subsequent dilemma of how to 'do' analysis of data which emerges from post-qualitative methodological contexts. Drawing on new feminist materialist theories and taking inspiration from the notion of data 'glows' and 'abducts', I illustrate how the affective intensities of encountering data can be productive of a different, more emergent meaning-making and knowledge production for both researcher and for participants. Through an unfixing of more traditional and particular ways of knowing and representing practitioners and practitioner learning, blurring the boundaries of life/experience/research/theory/method; I suggest that embodied, affective and relational readings of data can help us tell alternative, less predictable stories of both practitioner and researcher becomings. This approach suggests new possibilities for re-making and re-imagining professional learning and practices in the 21 st century.